Substitution of Dietary Sulfur Amino Acids by DL-2-hydroxy-4-Methylthiobutyric Acid Increases Remethylation and Decreases Transsulfuration in Weaned Piglets. Issue 3 (15th February 2019) - Rasch, Ilka; Görs, Solvig; Tuchscherer, Armin; Htoo, John K; Kuhla, Björn; Metges, Cornelia C
ABSTRACT: Background: DL-2-hydroxy-4-methylthiobutyric acid (DL-HMTBA), an L-methionine (L-Met) hydroxyl analogue, has been suggested to be a dietary L-Met source. How dietary DL-HMTBA compared with L-Met affects whole-body L-Met kinetics in growing individuals is unknown. Objectives: We determined to what extent DL-HMTBA supplementation of an L-Met–deficient diet affects whole-body L-Met and L-cysteine (L-Cys) kinetics, protein synthesis (PS), and the L-Met incorporation rate in liver protein (L-MetInc) compared with L-Met and DL-Met supplementation in a piglet model. Methods: Forty-five, 28-d-old weaned piglets (male, German Landrace) were allocated to 4 dietary groups: L-Met-deficient diet [Control: 69% of recommended L-Met plus L-Cys supply; 0.22% standardized ileal digestible (SID) L-Met; 0.27% SID L-Cys; n = 12] and Control diet supplemented equimolarly to 100% of recommended intake with either L-Met ( n = 12; LMET), DL-Met ( n = 11; DLMET), or DL-HMTBA ( n = 10; DLHMTBA). At 47 d of age, the piglets were infused with L-[1- 13 C; methyl- 2 H3 ]-Met and [3, 3- 2 H2 ]-Cys to determine the kinetics and PS rates. Plasma amino acid (AA) concentrations, hepatic mRNA abundances of L-Met cycle and transsulfuration (TS) enzymes, and L-MetInc were measured. Results: During feed deprivation, L-Met kinetics did not differ between groups, and were ≤3 times higher in the fed state ( P < 0.01). Remethylation (RM) was 31% and 45% higher in DLHMTBA than in DLMET and Control pigs, respectively, and the RM:transmethylation (TM) ratio was 50% higher in DLHMTBA than in LMET ( P < 0.05). Furthermore, TS and the TS:TM ratio were 32% lower in DLHMTBA than in LMET ( P < 0.05). L-MetInc was 42% lower in DLMET and DLHMTBA than in L-Met-deficient Control pigs, whereas plasma AA and hepatic mRNA abundances were similar among DL-HMTBA–, L-Met–, and DL-Met–supplemented pigs. Conclusions: In piglets, DL-HMTBA compared with L-Met and DL-Met supplementation increases RM and reduces the TS rate to conserve L-Met, but all 3 Met isomers support growth at a comparable rate.